Evaluation of serum levels of sCD30L ligand in patients with ovarian cancer in terms of selected clinico-pathological factors - Chudecka-Głaz, Anita; Rzepka-Górska, Izabella (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: The CD30L ligand is a membrane-associated glycoprotein expressed by activated CD4 + Th cells, macrophages, dendritic cells, and B lymphocytes. It binds to the CD30 receptor carried on activated and helper Th cells, inducing the immune response and apoptosis. The aim of this retrospective study was to determine the level of sCD30L in the serum of patients at diagnosis of ovarian cancer and at relapse and to assess the potential association of this ligand with selected clinico-pathologic factors. Material and methods : We studied 69 patients with ovarian cancer allocated to two groups: A – ovarian cancer at diagnosis, B – relapse of ovarian cancer and active growth of the tumor. Results : We found high levels of sCD30L in ovarian cancer patients. Levels at relapse (21.48 ng/ml) were significantly higher than at diagnosis (11.81 ng/ml). Poor response to first-line chemotherapy was accompanied by higher levels of sCD30L and by several other findings: resistance to platinum analogs was common, neoadjuvant chemotherapy was needed, relapse and death during two-year follow-up were frequent. Conclusions : Our present study might initially suggest that elevated concentration of sCD30L can be an important finding prognosticating a poor prognosis and is associated with platinum resistant and refractory cases of ovarian cancer. However, studies are needed on larger groups of patients.